(untitled) (International Journal of Engineering and Computer Science, 2016)
The publish/subscribe communication paradigm has gained high popularity. Publishers inject information into the pub/sub system and subscribers specify the events of interest by means of subscription. Traditional Content based pub/sub provide expressiveness and asynchronous nature but gives little attention to security. Existing approaches rely on traditional broker network that address security under restricted expressiveness or rely on network of semi-trusted brokers. This paper shows a new approach to provide authentication and confidentiality in BROKER_LESS pub/sub system by allowing subscribers to maintain credentials. Additionally we present Extensions of cryptographic methods, Multi credential routing that strengthens the weak subscription confidentiality.